1973
DOI: 10.1002/jmor.1051410405
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of feeding in miniature pigs

Abstract: The anatomy and physiology of feeding in miniature swine were studied, using gross dissection, electromyography, cinematography, and cineradiography.Small particles are preferred for ingestion, and large items are usually broken down outside of the oral cavity. The particles are initially picked up with the lower lip and then retrieved by the tongue; the tongue very rarely leaves the oral cavity. Geniohyoid, mylohyoid and digastric are the most active muscles during food collection.Mastication is fairly rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 28 publications
14
173
0
Order By: Relevance
“…Many of the species examined here can be included in Weijs's (1994) transverse chewing group-in several cases, a ''herbivorous'' morphotype. A late peak activity of the BDM has evolved multiple times in mammals that exhibit significant transverse movements during chewing, including rabbits (Weijs and Dantuma 1981), pigs (Herring and Scapino 1973;Huang 1994), alpacas , horses (Williams et al 2003), anthropoid primates (Hylander and Johnson 1994;Hylander et al 2000), sifakas (a lemuriform strepsirrhine) , and koalas (Crompton et al 2010). Thus, it remains to be seen whether our results apply broadly to other mammalian groups, including rodent and carnivoran morphotypes, or more specifically to this transverse chewing group of mammals.…”
Section: Discussionmentioning
confidence: 80%
“…Many of the species examined here can be included in Weijs's (1994) transverse chewing group-in several cases, a ''herbivorous'' morphotype. A late peak activity of the BDM has evolved multiple times in mammals that exhibit significant transverse movements during chewing, including rabbits (Weijs and Dantuma 1981), pigs (Herring and Scapino 1973;Huang 1994), alpacas , horses (Williams et al 2003), anthropoid primates (Hylander and Johnson 1994;Hylander et al 2000), sifakas (a lemuriform strepsirrhine) , and koalas (Crompton et al 2010). Thus, it remains to be seen whether our results apply broadly to other mammalian groups, including rodent and carnivoran morphotypes, or more specifically to this transverse chewing group of mammals.…”
Section: Discussionmentioning
confidence: 80%
“…These features suggested that expansion-contraction in the transverse (widening [AW, PDW and PVW] and thickening [RT and LT]) and sagittal (lengthening [RL and LL]) planes may better represent tongue internal kinematics during chewing and ingestion, respectively. Because sucking without lapping or licking occurs during water intake in pigs (Herring and Scapino, 1973), the tongue is subjected to more symmetric deformations with similar amplitudes in both transverse and sagittal planes during drinking (Fig. 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a number of similarities exist in the masticatory apparatus of rabbits and anthropoids, including a vertically deep face, position, and movements of the temporomandibular joint (Weijs and Dantuma, 1981;Crompton et al, 2006) as well as transverse jaw movements and jaw-muscle activity patterns (Weijs and Dantuma, 1981;Weijs et al, 1989;Hylander et al, 2000;Vinyard et al, 2008). Similar to many mammals, rabbit jaw-adductor activity patterns vary with dietary properties (Herring and Scapino, 1973;Luschei and Goodwin, 1974;Gorniak and Gans, 1980;Thexton et al, 1980;Weijs et al, 1987Weijs et al, , 1989Gans et al, 1990;Dessem and Druzinsky, 1992;Hylander et al, 1992Hylander et al, , 2000Hylander et al, , 2005, such that increased jaw-adductor recruitment results in elevated peak strains along the mandible and higher TMJ reaction forces (Weijs and de Jongh, 1977;Hylander, 1979aHylander, ,b,c, 1992Hylander et al, 1998;. Lastly, previous work on rabbit mandibular plasticity responses to postweaning alteration of dietary properties and masticatory stresses is consistent with similar experiments in a variety of other mammals (Beecher and Corruccini, 1981;Bouvier and Hylander, 1981, 1982, 1996aBeecher et al, 1983;Kiliardis et al, 1985;Bouvier, 1987Bouvier, , 1988Bouvier and Zimny, 1987;Block et al, 1988;Yamada and Kimmel, 1991;Ravosa et al, 2007bRavosa et al, , 2008a.…”
Section: Experimental Model Of Craniofacial Plasticitymentioning
confidence: 99%